Density, the Sustainability Multiplier: Some Myths and Truths with Application to Perth, Australia - Newman, Peter (Adver, SUSTDE, 2014)
The paper suggests that the divisive urban issue of density has criticalimportance for sustainability. It is particularly important to resolve for the low density cardependent cities of the world as they are highly resource consumptive. Ten myths aboutdensity and 10 truths about density are proposed to help resolve the planning issues socommonly found to divide urban communities. They are applied with data to Perth toillustrate the issues and how they can be resolved.